Evaluation of thyroid status in primary obese adults - Yeasmin, Nilufar; Yasmin, Hilary; Tasnin, Rehnuma; Masum, Tonmoy Reza; Haq, Tahniyah; Fariduddin, Md. (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Background: Obesity and hypothyroidism are two common clinical conditions that have been linked closely. Objective: To determine the status of thyroid function in primary obese adults. Methods: This cross-sectional study was conducted in the Department of Endocrinology, BMU from September 2022 to March 2025, enrolling 100 adults (aged 18-60 years) with obesity (BMI ≥25 kg/m²) and 50 adults (aged 18-60 years) with normal weight (BMI 18.5-22.9 kg/m²), all without known thyroid disorders. Secondary causes of obesity and conditions affecting thyroid function were excluded. Obesity parameters (body mass index, waist circumference, hip circumference, waist-hip ratio, waist-height ratio) were measured. Thyroid function tests, including free triiodothyronine (FT3), free thyroxine (FT4), thyroid-stimulating hormone (TSH), and anti-thyroid peroxidase antibody, were measured by chemiluminescent immunoassay. Results: The mean age of the obese and normal weight groups was 28.6 (8.5) years and 28.1 (8.8) years, respectively. Serum FT3 [3.2 (0.5) vs. 3.6 (0.4), pg/ml, p<0.001] and FT4 [1.1 (0.2) vs. 1.2 (0.2), ng/dl, p<0.001] levels were significantly lower while TSH [3.9 (3.3) vs. 1.6 (1.1), µIU/mL, p<0.001] levels were significantly higher in obese individuals compared to those of normal weight individuals. There was a significantly higher frequency of hypothyroidism (24% vs. 2% Total, 17% vs. 2% subclinical, and 7% vs. 0% overt, p=0.001) and anti-thyroid peroxidase antibody positivity (27% vs. 12%, p=0.037) in obese adults compared with normal weight adults. None of the participants had subclinical or overt thyrotoxicosis. Multiple linear regression revealed a significant negative correlation between FT4 and hip circumference (β = -2.266, 95% CI = -0.050 to -0.001). Conclusions: We found a significant association of hypothyroidism with obesity, irrespective of anti-thyroid peroxidase antibody status. [J Assoc Clin Endocrinol Diabetol Bangladesh, 2025;4(Suppl 1): S38]